Retinal Toxicity after Initial Administration of Nivolumab and Ipilimumab - Adnan Kilani; Efstathios Vounotrypidis; Susanna F. König; Armin Wolf (Case Reports in Ophthalmological Medicine)
Background. To present a rare case of a bilateral immune checkpoint inhibitor- (ICI-) induced photoreceptor injury with a bacillary layer detachment (BALAD) and a dissection of the photoreceptor inner and outer segment, accompanied by ICI-induced Vogt-Koyanagi-Harada- (VKH-) like uveitis after initial administration of nivolumab and ipilimumab. Case Presentation. A 52-year-old female with metastatic malignant cutaneous melanoma experiencing bilateral progressive visual acuity reduction, after treatment initiation with 1 mg/kg nivolumab and 3 mg/kg ipilimumab two weeks prior symptom onset. An extensive laboratory workup, including uveitis workup, onconeuronal and retinal antibodies, ruled out a paraneoplastic autoimmune disorder and a granulomatous disease. Furthermore, a B-scan was performed to exclude a posterior scleritis. Ensuing temporary treatment discontinuation of nivolumab and complete discontinuation of ipilimumab, treatment with high-dose systemic steroids was initiated, which resulted in alleviation of her symptoms and stability of ocular findings. Conclusions. ICIs can induce significant ocular side effects. As ocular inflammation can be well controlled using systemic steroids, treatment with ICIs can be continued whenever possible, in particular, if there is a good treatment response of the systemic malignancy.